2017
DOI: 10.3332/ecancer.2017.718
|View full text |Cite
|
Sign up to set email alerts
|

What are the personal and professional characteristics that distinguish the researchers who publish in high- and low-impact journals? A multi-national web-based survey

Abstract: PurposeThis study identifies the personal and professional profiles of researchers with a greater potential to publish high-impact academic articles.MethodThe study involved conducting an international survey of journal authors using a web-based questionnaire. The survey examined personal characteristics, funding, and the perceived barriers of research quality, work-life balance, and satisfaction and motivation in relation to career. The processes of manuscript writing and journal publication were measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
1
21
0
2
Order By: Relevance
“…Within international collaboration, our findings yielded mixed results. Inconsistent with Hypothesis 4, as well as recent research ( Paiva et al, 2017 ), is the finding that there is not a lower prevalence of Ibero-American collaboration among the internationally published journals in our sample. In hindsight, this might be expected, as the language of Brazil is most compatible with dialects from Ibero-American countries.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Within international collaboration, our findings yielded mixed results. Inconsistent with Hypothesis 4, as well as recent research ( Paiva et al, 2017 ), is the finding that there is not a lower prevalence of Ibero-American collaboration among the internationally published journals in our sample. In hindsight, this might be expected, as the language of Brazil is most compatible with dialects from Ibero-American countries.…”
Section: Discussionsupporting
confidence: 75%
“…This brings us back to the notion of lost science. With the higher impact factor journals publishing in English, the acceptance rate for non-native English speaking scholars is much lower than for their lingua franca counterparts ( Vasconcelos et al, 2007 ; Paiva et al, 2017 ). Likewise, the publishing performance for emerging nation journals is much lower than for their lingua franca counterparts ( Tijssen et al, 2006 ; Packer, 2014 ; Fradkin, 2015 , 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…This influence is clearly articulated in the Nature commentary, ‘The pressure to publish pushes down quality’ (Sarewitz, ). Whilst in several countries there are high rewards for being published in high impact journals, there is often a general pressure to publish (anywhere) and a lack of fluent English language precludes many researchers from being accepted in western journals (see Paiva et al ., ).…”
mentioning
confidence: 97%
“…The national origin of the institution may impact the publication and citation rates if the authors are from nondeveloped and non-English-speaking countries because there are barriers to access to advanced technology and language proficiency. [15][16][17] We found that from non-American countries, European followed by Asian institutions had the most articles in the American neurology and neuroradiology literature. In American neurosurgery journals, articles from Asia had an equal or greater number of contributions compared with European institutions.…”
Section: Discussionmentioning
confidence: 75%